Leadership styles and their relationship to organizational commitment among sports management workers A field study for the Directorate of Youth and Sports of the State of M'sila - زاوي, عزالدين; لوناس, عبد الله (sports creativity, 2025)
This study aimed to identify the relationship between leadership styles and organizational commitment in the Directorate of Youth and Sports of the State of M'sila through an applied study on the workers in the Directorate of Youth and Sports of the State of M'sila, who are (41) employees. The study used the descriptive research methodology, where a questionnaire was designed to collect data about the study variables, which were distributed to all employees in the directorate. After collecting the data, they were analyzed by appropriate statistical methods, and the study reached results, the most important of which is the presence of a high level of leadership styles and organizational commitment, according to the respondents’ assessment. In light of these results, the study presented a number of recommendations aimed at enhancing organizational commitment in the directorate.